2002
DOI: 10.1046/j.1432-1033.2002.03010.x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in ultrastructure and the occurrence of permeability transition in mitochondria during rat liver regeneration

Abstract: Mitochondrial bioenergetic impairment has been found in the organelles isolated from rat liver during the prereplicative phase of liver regeneration. To gain insight into the mechanism underlying this impairment, we investigated mitochondrial ultrastructure and membrane permeability properties in the course of liver regeneration after partial hepatectomy, with special interest to the role played by Ca 2+ in this process. The results show that during the first day after partial hepatectomy, significant changes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
39
0
2

Year Published

2003
2003
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(44 citation statements)
references
References 44 publications
3
39
0
2
Order By: Relevance
“…Although MPT can constitute a critical step of the apoptotic cascade, it has been found recently that this event would occur in the absence of reliable apoptosis during the prereplicative stage of LR. 6 Acute CCl 4 administration to rats constitutes another experimental model for inducing LR, which is remarkably similar (with some important differences) to that found after PH. 11 Here, the participation of mitochondrial oxidative function in the compensatory liver growth is completely unknown.…”
mentioning
confidence: 61%
See 2 more Smart Citations
“…Although MPT can constitute a critical step of the apoptotic cascade, it has been found recently that this event would occur in the absence of reliable apoptosis during the prereplicative stage of LR. 6 Acute CCl 4 administration to rats constitutes another experimental model for inducing LR, which is remarkably similar (with some important differences) to that found after PH. 11 Here, the participation of mitochondrial oxidative function in the compensatory liver growth is completely unknown.…”
mentioning
confidence: 61%
“…6 Despite these dramatic changes on mitochondrial ultrastructure and membrane permeability properties, apoptotic events did not proceed in the PHinduced regenerating liver. 6 Such alterations in mitochondrial membrane integrity have been related to growth factors or cytokine-induced mitochondrial oxidant production after PH. 25 However, we did not find an initial PH-induced onset of MPT, but rather this phenomenon occurred later in a lower magnitude.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…22 Further, there appears to be mitochondrial bioenergetic impairment during the prereplicative phase of liver regeneration, a change which has been attributed to Ca 2ϩ Ϫinduced permeability transition. 23 Compensatory pathways for generation of intracellular energy sources may need to be upregulated to account for such changes.…”
Section: Coupling Of Regeneration To a Metabolic Response In The Livermentioning
confidence: 99%
“…Indeed, increased LP has been found in liver homogenates from regenerating liver (Lambotte et al, 1989;Ueda et al, 1983), despite the fact that necrotic or apoptotic hepatocytes have not been observed at the onset of the proliferating liver (Oikawa and Novikoff, 1995). In addition, no changes in events characterizing the onset of mitochondrial permeability transition have been noticed in the regenerating liver (Guerrieri et al, 2002), and mitochondrial oxidative and phosphorylative activities are largely increased in PH rats (Hernández-Muñoz et al, 2003).…”
mentioning
confidence: 92%